Sulfur-doped phosphide polymorphic heterojunction full water decomposition electrocatalyst and preparation method thereof

Through the preparation of sulfur-doped phosphide multiform heterojunction catalyst, the problem of dual-function catalyst activity and stability in alkaline environment is solved, and efficient electrocatalytic water decomposition is achieved, especially maintaining long under high current density Time stability and high activity.

CN115679339BActive Publication Date: 2025-01-17DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110832633.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-22
Publication Date
2025-01-17
Estimated Expiration
2041-07-22

Smart Images

  • Figure CN115679339B_ABST
    Figure CN115679339B_ABST
Patent Text Reader

Abstract

The present invention provides a sulfur-doped phosphide polymorphic heterojunction full decomposition water electrocatalyst and a preparation method thereof. The catalyst chemical formula is S-M x P y / M a P b , wherein S represents sulfur, M represents any one of Fe, Co, Ni, Mo, Mn, and Cu, and P represents phosphorus. The fully decomposed water electrocatalyst is prepared by assembling the fully decomposed water electrocatalyst on a conductive carrier by a solvent thermal-phosphating-sulfur doping method. The phosphide polymorph heterojunction is prepared by adjusting the phosphating temperature and atmosphere. The obtained catalyst is a two-dimensional nanosheet structure with a high specific surface area and good conductivity. The best catalyst has a high conductivity in an alkaline electrolyte at 500 mA cm ‑2 The activity remained stable for more than 1000 hours at high current density without significant change. At the same time, the catalyst has excellent overall water splitting performance, 500mA cm ‑2 The overpotential of complete water splitting at high current density is only 460mV. This preparation method provides a feasible solution for the preparation of efficient and inexpensive phosphide complete water splitting electrocatalytic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic materials, and in particular relates to a sulfur-doped phosphide polymorphic heterojunction catalyst and a preparation method thereof, as well as an application in electrocatalytic water decomposition of hydrogen and oxygen. Background Art

[0002] As an ideal ultimate energy source, hydrogen energy is being widely developed and applied in fields such as hydrogen-oxygen fuel cells. Among them, the technology of using electricity generated by renewable energy to electrolyze water to produce hydrogen is the only way to achieve a green hydrogen economy and the development direction of hydrogen fuel cells in the future. The key to converting renewable energy storage into hydrogen energy is to reduce the cost of hydrogen production, that is, to improve the efficiency and stability of hydrogen production. The core lies in the development of efficient hydrogen and oxygen evolution catalysts. At present, alkaline water electrolysis is more mature and widely used than acidic water electrolysis technology. It has the advantages of low cost, simple process, convenient operation, and high purity of hydrogen produced (up to 99% to 99.99%). However, the most excellent hydrogen evolution catalyst is still platinum-based precious metals, and the oxygen evolution catalyst depends on iridium oxide and ruthenium oxide. Platinum, iridium, and ruthenium are all precious metals with small reserves on the earth, which is not conducive to their promotion and application in industry. Therefore, it is imperative to develop non-precious metal catalysts that are abundant on the earth.

[0003] Previously, researchers have found that transition metal carbides, nitrides, sulfides, etc. have bifunctional catalytic activity for both hydrogen and oxygen evolution, but the hydrogen and oxygen evolution catalysts reported so far show high activity in acidic and alkaline media, respectively. How to prepare bifunctional transition metal catalysts with high activity and high stability in alkaline environments is still a difficult problem to be solved in the field of electrocatalytic water splitting. x P y (CoP、Ni 2 P, Cu 3 P, MoP, etc.) is a type of intercalated compound formed by P atoms entering the transition metal lattice. It has high chemical stability, high catalytic activity and good reaction kinetics, and is widely used in hydrodesulfurization, electrocatalytic water splitting and other fields. Transition metal phosphides show high electrocatalytic hydrogen evolution performance, but low electrocatalytic oxygen evolution performance, which limits their application as bifunctional catalysts. The currently reported bifunctional phosphide catalysts for alkaline full water electrolysis require a voltage of 1.6V to reach 10mA cm -2 The current density is too low and the efficiency of catalytic water electrolysis cannot meet the requirements of commercialization.

[0004] Domestic and foreign scholars have used strategies such as heteroatom doping, defect construction, and composite structure construction to improve the performance of catalysts for complete water splitting. For example, Daniel et al. reported that Fe doping was used to change the electronic structure of phosphide and improve the efficiency and stability of the catalyst (Proceedings of the National Academy of Sciences, 2017, 114(7): 1486-1491.). Qian et al. reported that the CoP / FeNi-LDH composite structure promoted OH - The adsorption and activation of phosphides greatly reduces the overpotential compared to a single catalyst (Angewandte Chemie International Edition, 2019, 58(34): 11903-11909.). For phosphides, the ratio of M and P determines the properties of the material. When x:y≥1, the material has a high conductivity, but a weak ability to activate water molecules. When x:y<1, especially x:y<2, the electron-rich properties of P can effectively adsorb protons and promote the activation of water molecules, but the reduction in the content of MM bonds greatly inhibits the conductivity of the material. So far, there have been no reports on the use of heterojunctions constructed using polymorphs of phosphides themselves for the complete decomposition of water. Key scientific and technological issues such as catalyst synthesis and structure-activity relationship of electrocatalytic performance and structural optimization design need to be urgently addressed. Summary of the invention

[0005] The purpose of the present invention is to provide a sulfur-doped phosphide polymorphic heterojunction catalyst for electrocatalytic water splitting with high activity and high stability. The catalyst prepared by the invention is supported on a conductive substrate and has a two-dimensional ultra-thin structure, a large specific surface area, and high conductivity. At the same time, it can greatly reduce the overpotential and Tafel slope of hydrogen and oxygen evolution. -2 The performance can be maintained for 1000h without attenuation under the current density, and the activity and stability are significantly improved compared with the single-component phosphide catalyst. Therefore, the sulfur-doped phosphide polymorphic heterojunction catalyst has a good application prospect in the overall water splitting.

[0006] The technical solution of the present invention is specifically as follows:

[0007] In one aspect, the present invention provides a sulfur-doped phosphide polymorph heterojunction full water splitting electrocatalyst, wherein the catalyst is a heterostructure of a sulfur-doped polymorph phosphide, and the chemical formula of the catalyst is SM x P y / M a P b, wherein S represents sulfur, M represents any one of Fe, Co, Ni, Mo, and Mn, and P represents phosphorus; the value ranges of x, y, a, and b are: 1≤x≤12, 1≤y≤5, 1≤a≤12, 1≤b≤5; the S content in the catalyst is 0.2at.%-10at.%; the morphology of the catalyst is a two-dimensional nanosheet.

[0008] Based on the above scheme, preferably, the value ranges of x, y, a, and b are: 1≤x≤4, 1≤y≤4, 1≤a≤2, 1≤b≤4; the content of S in the catalyst is 1at.%4at.%; the M in the heterogeneous structure is x P y With M a P b The ratio is 1:10 to 10:1; the M is Co; the thickness of the nanosheet is 1-10 nm, and the size of the nanosheet is 50-5000 nm.

[0009] Based on the above scheme, preferably, M in the heterostructure x P y With M a P b The ratio is 1:4 to 4:1; the thickness of the nanosheet is 1-10nm; more preferably 4nm, and the size of the nanosheet is 200-2000nm; more preferably 1000nm.

[0010] On the other hand, the present invention provides a method for preparing the above-mentioned catalyst, wherein the catalyst is prepared by a solvent thermal-phosphating-sulfur doping method and assembled on a conductive carrier, specifically comprising the following steps:

[0011] (1) Using metal salts of M as precursors, two-dimensional MO was solvothermally synthesized in a mixed solution of P123, ethanol, water, hexamethylenetetramine, and ethylene glycol. x Nanosheets;

[0012] (2) MO synthesized in step (1) x Nanosheets are used as precursors. After being mixed with a phosphorus source, MO is converted into x Topological transformation into phosphide heterojunction nanosheets;

[0013] (3) Using the phosphide heterojunction nanosheets synthesized in step (2) as a precursor, adding a sulfur source and a conductive carrier, and synthesizing a supported phosphide heterojunction catalyst by a solvent thermal method.

[0014] Based on the above scheme, preferably, in step (1), the solvent thermal synthesis reaction is carried out in a hydrothermal kettle, the hydrothermal temperature is 100-250°C, and the hydrothermal reaction time is 0.5-24h; the metal salt of M is one of the acetate, nitrate, chloride, and acetylacetone compounds of M; the mass ratio of P123, ethanol, water, ethylene glycol, metal salt and hexamethylenetetramine is 1:10:1:10:0.01:0.01-1:100:10:10:10:10; the mixing method of the raw materials in step (1) is: adding P123 to ethanol, then adding water, stirring evenly to obtain solution 1; then adding the metal salt precursor of M to solution 1, stirring evenly, then adding hexamethylenetetramine, and then adding ethylene glycol, stirring evenly to obtain the mixed solution.

[0015] Based on the above scheme, preferably, in step (1), the hydrothermal temperature is 100-190; more preferably 170°C, the hydrothermal reaction time is 1-10h; more preferably 2h; the metal salt of M is acetate; the mass ratio of P123, ethanol, water, ethylene glycol, metal salt and hexamethylenetetramine is 1:10:1:20:0.3:0.02 to 1:50:10:40:3:0.2, more preferably 1:60:5:20:1.77:0.035.

[0016] Based on the above scheme, preferably, in step (2), the phosphorus source is sodium hypophosphite, and the in-situ phosphating is carried out in a tubular furnace with an air pressure of 0.1-1 MPa and an atmosphere of N 2 , the gas flow rate is 10-200sccm, and the temperature of the tube furnace is 200-900°C; in step (3), the sulfur source is thioacetamide, thiourea or thiol; the solvent for the solvent thermal synthesis is a C1-5 alcohol; the mass ratio of the solvent to the sulfur source is 100:1 to 1000:1; the temperature of the solvent thermal synthesis is 80-200°C, and the time is 0.5 to 48h; the conductive carrier is one of foamed nickel, nickel mesh, Raney nickel, foamed copper, foamed iron, foamed cobalt, carbon cloth, and carbon paper.

[0017] Based on the above scheme, preferably, in step (2), the gas pressure in the tube furnace is 0.2-0.5MPa, more preferably 0.1MPa, the gas flow rate is 10-100sccm, more preferably 50sccm, and the temperature of the tube furnace is 100-500°C, more preferably 350°C; in step (3), the sulfur source is thioacetamide, and the solvent for the solvent thermal synthesis is ethanol; the mass ratio of the solvent to the sulfur source is 200:1 to 500:1, more preferably 500:1; the temperature of the solvent thermal synthesis is 100-190°C, more preferably 120°C, and the time is 1-10h, more preferably 6h; the conductive carrier is a nickel mesh.

[0018] As a further preferred embodiment of the above scheme, the present invention provides a method for preparing a sulfur-doped phosphide polymorph heterojunction complete water decomposition catalyst, and the specific steps of the method are as follows:

[0019] A: Add 50–500 mg of P123 to 5–50 mL of ethanol, then add 0.5–5 mL of water and stir well to obtain solution 1.

[0020] B: 0.177–1.77 g of metal salt precursor is added to solution 1, stirred evenly, and then 5–50 mg of hexamethylenetetramine is added, followed by 10–20 mL of ethylene glycol, stirred evenly, to obtain solution 2;

[0021] C: Place solution 2 in a 25–250 mL hydrothermal reactor and react at 100–200 °C for 1–10 h. After washing, a two-dimensional MO is obtained. x ;

[0022] D: The obtained two-dimensional MO x Mix with 50–500 mg sodium hypophosphite and phosphate at 200–600 °C for 2–10 h in a N atmosphere. 2 , a two-dimensional phosphide polymorphic heterojunction catalyst is prepared;

[0023] E: Disperse 10–100 mg of the prepared two-dimensional phosphide polymorphic heterojunction catalyst in 5–50 mL of ethanol, add 30–300 mg of a S-containing precursor, stir thoroughly, and react the mixed solution in a 25–250 mL hydrothermal autoclave at 100–200° C. for 2–24 h. After the reaction, wash with ethanol and secondary water, respectively, and dry to obtain the catalyst.

[0024] In another aspect, the present invention provides an application of the above catalyst in electrocatalytic decomposition of hydrogen and oxygen from water. The specific reaction conditions are: the catalyst supported by the conductive carrier obtained in step E is directly used as a hydrogen evolution electrode and an oxygen evolution electrode to perform an electrocatalytic full water decomposition reaction in a two-electrode system.

[0025] Based on the above scheme, preferably, the electrolyte used in the electrocatalytic water decomposition reaction is an alkaline electrolyte, the base is one of KOH, NaOH, LiOH, CsOH, preferably KOH; the concentration of the alkaline electrolyte is 0.5-10M, preferably 1M.

[0026] Beneficial Effects

[0027] The present invention discloses a simple and low-cost method for synthesizing M having a polymorphic heterojunction structure. x P y / M a P bCatalytic material. As a non-precious metal bifunctional catalyst, the present invention has the following advantages:

[0028] (1) The sulfur-doped phosphide catalytic material prepared by the present invention has a polymorphic heterostructure. The phosphide polymorphic heterojunction is prepared by adjusting the phosphating temperature and atmosphere. The relative ratio of the heterostructure can be adjusted between 1:10 and 10:1. The synthesis method is simple and the production method is flexible, which can be adjusted according to different needs.

[0029] (2) The sulfur-doped phosphide polymorph heterostructure provided by the present invention has a two-dimensional structure, a high specific surface area, a high electrical conductivity, and excellent hydrogen and oxygen evolution activity and stability. The electrocatalytic hydrogen evolution capacity is 50 mA cm under alkaline conditions. -2 , 500mA cm -2 The overpotential at the current density is only 50mV and 150mV, and the electrocatalytic oxygen evolution is 50mA cm -2 and 500mA cm -2 The overpotential is only 240mV and 340mV at the current density, and at 500mA cm -2 The activity remained stable for more than 1000 hours at high current density without significant change. At the same time, the catalyst has excellent overall water splitting performance. -2 The overpotential for complete water decomposition at high current density is only 490 mV. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The S-CoP / Co prepared in Example 1 2 (A) Low-magnification and (B) high-magnification transmission images of P polymorph heterojunction.

[0031] Figure 2 The S-CoP / Co prepared in Example 1 2 Linear scans of (A) electrocatalytic hydrogen evolution and (B) electrocatalytic oxygen evolution of P polymorph heterojunction electrode in 1 M KOH.

[0032] Figure 3 The S-CoP / Co prepared in Example 1 2 Linear scan of the complete water splitting of the P polymorph heterojunction electrode in 1 M KOH.

[0033] Figure 4 The S-CoP / Co prepared in Example 1 2 P polymorph heterojunction electrode in 1 M KOH at 500 mA cm -2 Stability diagram of electrocatalytic oxygen evolution at current density >1000h.

[0034] Figure 5 The S-NiP / Ni prepared in Example 2 2Linear scan of the complete water splitting of the P polymorph heterojunction electrode in 1 M KOH. DETAILED DESCRIPTION

[0035] In order to further illustrate the present invention, the following examples are listed and described in conjunction with the accompanying drawings, but they do not limit the scope of the invention defined by the claims of the present invention. Unless otherwise specified, the raw materials used in the examples are all commercially available conventional raw materials.

[0036] Example 1

[0037] 20 mg P123, 0.5 g cobalt acetate, and 10 mg hexamethylenetetramine were added to 20 mL ethanol, 1 mL water, and 10 mL ethylene glycol solution and stirred evenly; the above solution was transferred to a reactor and reacted at 150 ° C for 5 h, and then washed and dried to obtain two-dimensional CoO x ; The obtained two-dimensional CoO x After mixing with 200 mg of sodium hypophosphite, phosphating was performed at 300 °C for 5 h in a N atmosphere. 2 , a two-dimensional phosphide polymorph heterojunction catalyst was prepared; 50 mg of the prepared two-dimensional cobalt phosphide polymorph heterojunction catalyst was dispersed in 20 mL of ethanol containing 50% thioacetamide precursor and stirred thoroughly, and a 1 cm*1 cm nickel foam was added, and then the mixed solution was reacted in a 50 mL hydrothermal kettle at 120°C for 10 h. After the reaction, it was washed with ethanol and secondary water respectively, and dried to obtain the catalyst S-CoP / Co supported on the nickel foam. 2 P.

[0038] The catalyst supported by the conductive carrier prepared in Example 1 was directly used as a hydrogen evolution electrode and an oxygen evolution electrode to carry out an electrocatalytic water decomposition reaction in a two-electrode system. The electrolyte used was 1M KOH. The implementation results are shown in FIG. Figure 2-4 As shown. Electrocatalytic hydrogen evolution at 50 mA cm under alkaline conditions -2 , 500mA cm -2 The overpotential at the current density is only 50mV and 150mV, and the electrocatalytic oxygen evolution is 50mA cm -2 and 500mA cm -2 The overpotential is only 240mV and 340mV at the current density, and at 500mA cm -2 The activity remained stable for more than 1000 hours at high current density without significant change. At the same time, the catalyst has excellent overall water splitting performance. -2 The overpotential for complete water decomposition at high current density is only 490 mV.

[0039] Example 2

[0040] 40 mg P123, 0.5 g nickel acetate, and 20 mg hexamethylenetetramine were added to 20 mL ethanol, 2 mL water, and 20 mL ethylene glycol solution and stirred evenly; the above solution was transferred into a reactor and reacted at 150 ° C for 5 h, and then washed and dried to obtain two-dimensional NiO x The obtained two-dimensional NiO x The catalyst was mixed with 400 mg of sodium hypophosphite and phosphated at 300 ° C for 5 h to prepare a two-dimensional phosphide polymorphic heterojunction catalyst; 100 mg of the prepared two-dimensional nickel phosphide polymorphic heterojunction catalyst was dispersed in 40 mL of ethanol containing thioacetamide precursor and stirred thoroughly, and a 1 cm*1 cm nickel mesh was placed in the mixed solution. The mixed solution was then reacted in a hydrothermal reactor at 120 ° C for 10 h to obtain a catalyst S-NiP / Ni supported on nickel foam. 2 P.

[0041] The obtained catalyst was electrocatalyzed to generate hydrogen at 50 mA cm in 1 M KOH electrolyte under alkaline conditions. -2 , 500mA cm -2 The overpotential at the current density is only 70mV and 170mV, and the electrocatalytic oxygen evolution is 50mA cm -2 and 500mA cm -2 The overpotential is only 260mV and 360mV at the current density, and at 500mA cm -2 The oxygen evolution was stable for more than 500 hours at high current density without significant change in activity. At the same time, the catalyst has excellent overall water splitting performance. -2 The overpotential for complete water decomposition at high current density is only 530 mV.

[0042] Example 3

[0043] 30 mg P123, 0.5 g ferric acetylacetonate, and 20 mg hexamethylenetetramine were added to 20 mL ethanol, 2 mL water, and 30 mL ethylene glycol solution and stirred evenly. The above solution was transferred to a hydrothermal autoclave and reacted at 150 ° C for 5 h, and then washed and dried to obtain two-dimensional FeO x The obtained two-dimensional FeO x After mixing with 400 mg of sodium hypophosphite, phosphating was performed at 300 °C for 5 h in a N atmosphere. 2 , a two-dimensional phosphide polymorph heterojunction catalyst was prepared; 100 mg of the prepared two-dimensional iron phosphide polymorph heterojunction catalyst was dispersed in 40 mL of ethanol containing a thiourea precursor and stirred thoroughly, and then a 1 cm*1 cm nickel mesh was placed, and then the mixed solution was reacted in a 50 mL hydrothermal kettle at 130°C for 10 h to obtain the catalyst S-FeP / Fe supported on the nickel mesh. 2 P.

[0044] The obtained catalyst was electrocatalyzed to generate hydrogen at 50 mA cm in 1 M KOH electrolyte under alkaline conditions. -2 , 500mA cm -2 The overpotential at the current density is only 70mV and 170mV, and the electrocatalytic oxygen evolution is 50mA cm -2 and 500mA cm -2 The overpotential is only 250mV and 350mV at the current density, and at 500mA cm -2 The oxygen evolution was stable for more than 600 hours at high current density without significant change in activity. At the same time, the catalyst has excellent overall water splitting performance. -2 The overpotential for complete water decomposition at high current density is only 520 mV.

[0045] Example 4

[0046] 50 mg P123, 0.5 g cobalt acetylacetonate, and 20 mg hexamethylenetetramine were added to 30 mL ethanol, 5 mL water, and 20 mL ethylene glycol solution and stirred evenly; the above solution was transferred into a reactor and reacted at 180 ° C for 10 h, and CoO was obtained after washing and drying. x ; The obtained CoO x After mixing with 600 mg of sodium hypophosphite, the mixture was phosphated at 300 ° C for 3 h in an Ar atmosphere to prepare a phosphide polymorph heterojunction catalyst; 100 mg of the prepared cobalt phosphide polymorph heterojunction catalyst was dispersed in 60 mL of ethanol containing a thiourea precursor and stirred thoroughly, and then placed in a 1 cm*2 cm nickel mesh. The mixed solution was then reacted in a 50 mL hydrothermal reactor at 130 ° C for 10 h to obtain a catalyst S-CoP supported on the nickel mesh. 2 / Co 2 P.

[0047] The obtained catalyst was electrocatalyzed to generate hydrogen at 50 mA cm in 1 M KOH electrolyte under alkaline conditions. -2 , 500mA cm -2 The overpotential at the current density is only 80mV and 180mV, and the electrocatalytic oxygen evolution rate is 50mA cm -2 and 500mA cm -2 The overpotential is only 260mV and 360mV at the current density, and at 500mA cm -2 The oxygen evolution was stable at high current density for more than 700 hours without significant change in activity. At the same time, the catalyst has excellent overall water splitting performance. -2 The overpotential for complete water decomposition at high current density is only 540 mV.

[0048] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A sulfur-doped phosphide polymorphic heterojunction full water splitting electrocatalyst, characterized in that: The catalyst is a heterogeneous structure of sulfur-doped polymorphic phosphide, and the chemical formula of the catalyst is SM x P y / M a P b , wherein S represents sulfur, M represents any one of Fe, Co, Ni, Mo, Mn, Cu, and P represents phosphorus; the value ranges of x, y, a, and b are: 1≤x≤12, 1≤y≤5, 1≤a≤12, 1≤b≤5; the content of S in the catalyst is 0.2at.%-10at.%; M in the heterogeneous structure x P y With M a P b The ratio is 1:10 to 10:1; the morphology of the catalyst is a two-dimensional nanosheet; The method for preparing the catalyst, wherein the catalyst is prepared by a solvent thermal-phosphating-sulfur doping method and assembled on a conductive carrier, specifically comprises the following steps: (1) Using metal salts of M as precursors, two-dimensional MO was solvothermally synthesized in a mixed solution of P123, ethanol, water, hexamethylenetetramine, and ethylene glycol. x Nanosheets; (2) MO synthesized in step (1) x The nanosheets are used as precursors, mixed with a phosphorus source, and then the MO x Topological transformation into phosphide heterojunction nanosheets; (3) Using the phosphide heterojunction nanosheets synthesized in step (2) as a precursor, adding a sulfur source and a conductive carrier, and synthesizing a supported phosphide heterojunction catalyst by a solvent thermal method.

2. The catalyst according to claim 1, characterized in that: The value ranges of x, y, a, and b are: 1≤x≤4, 1≤y≤4, 1≤a≤2, 1≤b≤4; the S content in the catalyst is 1at.%-4at.%; M is Co; the thickness of the nanosheet is 1-10nm, and the size of the nanosheet is 50-5000nm.

3. The catalyst according to claim 2, characterized in that: Heterostructure x P y With M a P b The ratio is 1:4 to 4:1; the thickness of the nanosheet is 1-10 nm, and the size of the nanosheet is 200-2000 nm.

4. The catalyst according to claim 1, characterized in that In step (1), the solvent thermal synthesis reaction is carried out in a hydrothermal reactor, the hydrothermal temperature is 100-250° C., and the hydrothermal reaction time is 0.5-24 h; the metal salt of M is one of acetate, nitrate, chloride, and acetylacetone compounds of M; the mass ratio of P123, ethanol, water, ethylene glycol, metal salt, and hexamethylenetetramine is 1:10:1:10:0.01:0.01 to 1:100:10:10:10:10; The raw materials in step (1) are mixed as follows: P123 is added to ethanol, and then water is added, and stirred evenly to obtain solution 1; then the metal salt precursor of M is added to solution 1, and stirred evenly, and then hexamethylenetetramine is added, and then ethylene glycol is added, and stirred evenly to obtain the mixed solution.

5. The catalyst according to claim 4, characterized in that In step (1), the hydrothermal temperature is 100-190° C., and the hydrothermal reaction time is 1-10 h; the metal salt of M is acetate; and the mass ratio of P123, ethanol, water, ethylene glycol, metal salt and hexamethylenetetramine is 1:10:1:20:0.3:0.02 to 1:50:10:40:3:0.

2.

6. The catalyst according to claim 1, characterized in that In step (2), the phosphorus source is sodium hypophosphite, the in-situ phosphating is carried out in a tubular furnace, the gas pressure in the tubular furnace is 0.1-1MPa, the atmosphere of the tubular furnace is N2, the gas flow rate is 10-200sccm, and the temperature of the tubular furnace is 200-900°C; in step (3), the sulfur source is thioacetamide, thiourea or thiol; the solvent for the solvent thermal synthesis is a C1-C5 alcohol; the mass ratio of the solvent to the sulfur source is 100:1 to 1000:1; the temperature of the solvent thermal synthesis is 80-200°C, and the time is 0.5-48h; the conductive carrier is one of foamed nickel, nickel mesh, Raney nickel, foamed copper, foamed iron, foamed cobalt, carbon cloth, and carbon paper.

7. The catalyst according to claim 6, characterized in that In step (2), the gas pressure in the tube furnace is 0.2-0.5MPa, and the gas flow rate is 10-100sccm; in step (3), the sulfur source is thioacetamide, and the solvent for the solvent thermal synthesis is ethanol; the mass ratio of the solvent to the sulfur source is 200:1 to 500:1; the temperature of the solvent thermal synthesis is 100-190°C, and the time is 1-10h; the conductive carrier is a nickel mesh.

8. Use of the catalyst according to any one of claims 1 to 3 in electrocatalytic decomposition of hydrogen and oxygen from water.

9. The use according to claim 8, characterized in that: The electrolyte used in the electrocatalytic water decomposition reaction is an alkaline electrolyte, and the alkali is one of KOH, NaOH, LiOH, and CsOH; the concentration of the alkaline electrolyte is 0.5-10M.

Citation Information

Patent Citations

  • Sulfur-doped cobalt phosphide - carbon nanofiber composite material and preparation method thereof

    CN107460725A

  • Sulfur-doped nickel phosphide catalyst for hydrogen evolution reaction and preparation method thereof

    CN107502919A